2021
DOI: 10.1093/glycob/cwab106
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic tracing of sugar metabolism reveals the mechanisms of action of synthetic sugar analogs

Abstract: Synthetic sugar analogs are widely applied in metabolic oligosaccharide engineering (MOE) and as novel drugs to interfere with glycoconjugate biosynthesis. However, mechanistic insights on their exact cellular metabolism over time are mostly lacking. We combined ion-pair UHPLC-QqQ mass spectrometry using tributyl- and triethylamine buffers for sensitive analysis of sugar metabolites in cells and organisms and identified low abundant nucleotide sugars, such as UDP-arabinose in human cell lines and CMP-sialic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…Firstly, we analyzed the production of CMP-Sia in wildtype flies and CSAS mutants by a liquid chromatography-mass spectrometry approaches (see Materials and Methods). A prominent peak corresponding to CMP-Sia was detected in wildtype flies as shown before (Scherpenzeel et al, 2021), while no CMP-Sia was found in CSAS mutants. Transgenic rescue using UAS-GAL4 system resulted in the restoration of CMP-Sia biosynthesis in the mutants (Fig 4A-B).…”
Section: Resultssupporting
confidence: 76%
“…Firstly, we analyzed the production of CMP-Sia in wildtype flies and CSAS mutants by a liquid chromatography-mass spectrometry approaches (see Materials and Methods). A prominent peak corresponding to CMP-Sia was detected in wildtype flies as shown before (Scherpenzeel et al, 2021), while no CMP-Sia was found in CSAS mutants. Transgenic rescue using UAS-GAL4 system resulted in the restoration of CMP-Sia biosynthesis in the mutants (Fig 4A-B).…”
Section: Resultssupporting
confidence: 76%
“…4, with details in Fig. S5) [41]. The overexpression of ST6GAL1 in hCK WT and hCK-B3GNT2 cells compared to MDCK WT cells resulted in elevated levels of sialylation and thereby lower levels of available CMP-Neu5Ac, which was also demonstrated in the sugar nucleotide analysis.…”
Section: Resultsmentioning
confidence: 85%
“…The supernatant was taken and dried in the vacuum concentrator. Samples were frozen at −80°C until analysis using an ion-pair UHPLC-QqQ 1290-6490 Agilent mass spectrometer by Glycomscan BV (Oss, the Netherlands) [41].…”
Section: Methodsmentioning
confidence: 99%
“…Another hypothesis regarding the diffuse staining of labeled GCs into cells is supported by a recent study showing that incubation of human fibroblasts with Ac 4 ManNAl (Ac 4 ManNPoc) resulted in biosynthesis of not only CMP-SiaNAl, but also UDP-HexNAl 42 . The latter may come from the hijacking of unnatural ManNAc by GlcNAc-2-epimerase (RENBP), leading to the biosynthesis of chemically modified UDP-GlcNAc through the salvage pathway 43 (Fig.…”
Section: Discussionmentioning
confidence: 95%